Comparative efficacy of different exercise modalities on metabolic profiles and liver functions in non-alcoholic fatty liver disease: a network meta-analysis - Huang, Mingming; Yang, Jiafa; Wang, Yihao; Wu, Jian (Frontiers in Physiology, 2024)
Research evidence suggests that exercise is a potent therapeutic strategy for non-alcoholic fatty liver disease (NAFLD). Many investigations have delved into the curative potential of diverse exercise regimens on NAFLD. This investigation synthesizes findings from randomized controlled trials via a network meta-analysis to evaluate the efficacy of exercise-based interventions on NAFLD.We conducted a search across five electronic databases(Web of Science, EMBASE, PubMed, SCOPUS, and CNKI)to identify randomized controlled trials (RCTs) comparing the effects of different exercise modalities on metabolic profiles and liver functions in patients with NAFLD. The literature search was comprehensive up to December 15, 2023. The selected studies were subjected to a rigorous quality appraisal and risk of bias analysis in accordance with the Cochrane Handbook's guidelines, version 5.1.0. We employed Stata/MP 17 for the network meta-analysis, presenting effect sizes as standardized mean differences (SMD).Results: This study aggregated results from 28 studies, involving a total of 1,606 participants. The network meta-analysis revealed that aerobic exercise was the most effective intervention for improving BMI in patients with NAFLD, demonstrating a significant decrease in BMI (-0.72, 95%CI: -0.98 to -0.46; P < 0.05; Surface Under the Cumulative Ranking (SUCRA) = 79.8%). HIIT was the top intervention for enhancing HDL-C (0.12, 95% CI: 0.04 to 0.20; P < 0.05; SUCRA = 76.1%).Resistance exercise was the most effective for reducing LDL-C (-0.20, 95% CI: -0.33 to -0.06; P < 0.05; SUCRA = 69.7%). Mind-body exercise showed superior effectiveness in improving TC (-0.67, 95%